Christmas from the heart - Roberts, Sheila, 1951- (Mira, 2019)
Olivia Berg's charity, Christmas from the Heart, has helped generations of families in need in Pine River, Washington, but this year might be the end of the road. Hightower Enterprises, one of their biggest donors since way back when Olivia's grandmother ran the charity, has been taken over by Ebenezer Scrooge the Second, aka CFO Guy Hightower, and he's declared there will be no more money coming to Christmas from the Heart. Guy is simply being practical. Hightower Enterprises needs to tighten its belt, and when you don't have money to spare, you don't have money to share. You'd think even the pushy Olivia Berg could understand that. With charitable donations dwindling, Olivia's Christmas budget depends on Hightower's contribution. She's focused her whole life on helping this small town, even putting her love life on hold to support her mission. When Guy's Maserati breaks down at the edge of the Cascade foothills, he's relieved to be rescued by a pretty young woman who drives him to the nearby town of Pine River. Until he realizes his rescuer is none other than Olivia Berg. What's a Scrooge to do? Plug his nose and eat fruitcake and hope she doesn't learn his true identity before he can get out of town. What could go wrong?